Dr. Blake Raggio — Deep Plane Facelift — Birmingham - Raggio, Blake (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Blake Raggio, practicing in Birmingham, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002982; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; birmingham